2022
DOI: 10.3389/fgene.2022.859185
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Paternal 20q13.2-q13.32 Deletion Patient With Growth Retardation Improved by Growth Hormone

Abstract: Interstitial chromosome 20q deletions, containing GNAS imprinted locus, are rarely reported in the past. Hereby, we presented a Chinese boy with a novel 4.36 Mb deletion at paternal 20q13.2-13.32, showing feeding difficulty, malnutrition, short stature, lower limb asymmetry, sightly abnormal facial appearance and mild intellectual abnormality. With 3 years’ growth hormone treatment, his height was increased from 90 to 113.5 cm. This report is the first time to describe the outcome of clinical treatment on a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Moreover, the facial features of a broad forehead, triangular face, and sparse eyebrows were common. More than half of the patients (4/7) met the Netchine–Harbison clinical scoring system criteria and were diagnosed with Silver–Russell syndrome (SRS) (Aldred et al, 2002; Balasubramanian et al, 2015; Butler et al, 2013; Geneviève et al, 2005; Liu et al, 2022; Solomon et al, 2011). The phenotype in this study is remarkably different from those previously reported for 20q13.32 deletion mutation, which may have typical PHP characteristics because the deletion of the 20q13.32 segment destroys the maternal Gsa protein activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the facial features of a broad forehead, triangular face, and sparse eyebrows were common. More than half of the patients (4/7) met the Netchine–Harbison clinical scoring system criteria and were diagnosed with Silver–Russell syndrome (SRS) (Aldred et al, 2002; Balasubramanian et al, 2015; Butler et al, 2013; Geneviève et al, 2005; Liu et al, 2022; Solomon et al, 2011). The phenotype in this study is remarkably different from those previously reported for 20q13.32 deletion mutation, which may have typical PHP characteristics because the deletion of the 20q13.32 segment destroys the maternal Gsa protein activity.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion mutations comprising the 20q13.32 region of GNAS are rare; to date, only eight patients with such mutations have been reported in six studies (including de novo, paternal, and maternal mutations). The phenotypic features of these patients are mainly characterized by feeding difficulties, slow growth, abnormal facial appearance, and mental retardation, with some patients showing an incomplete AHO phenotype (Aldred et al, 2002; Balasubramanian et al, 2015; Butler et al, 2013; Geneviève et al, 2005; Liu et al, 2022; Solomon et al, 2011). This may be different from the typical PHP phenotype that includes PTH and TSH resistance, short bones, short stature, and stocky build (Mantovani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%